Urinary albumin-to-creatinine ratio in patients with hypertension and risk of major cardiovascular events - Morten Schou; Anders Nissen Bonde; Nicholas Carlson; Casper Binding; Mariam Elmegaard; Deewa Zahir Anjum (Open Heart)
Introduction/aims Evaluation of urinary albumin-to-creatinine ratio (uACR) is a key component in the management of hypertension, yet there is a lack of data on the association between uACR and major cardiovascular events (MACEs) in large hypertensive cohorts, and it is also unknown how often uACR is measured among these patients.We aimed to evaluate the usage of uACR in a nationwide population of patients with hypertension. Furthermore, we sought to assess the risk of cardiorenal events according to uACR, among patients with hypertension.Methods We used Danish nationwide registries to identify patients who initiated antihypertensive treatment. The patients were grouped at treatment initiation according to uACR: normoalbuminuria, microalbuminuria, macroalbuminuria and no uACR measurement, and followed for 2 years, to evaluate the risk of a MACE, hospitalisation for heart failure (HF), 40% decline in estimated glomerular filtration rate (eGFR) and end-stage kidney disease (ESKD) according to uACR.Results We included 144 644 patients, of whom 116 039 (80%) did not have their uACR evaluated at treatment initiation. Patients with macroalbuminuria comprised the greatest 2 year absolute risk of MACE (5.3%, 95% CI: 4.0% to 6.6%) and had a greater risk of MACE (HR: 2.02, 95% CI: 1.54 to 2.66), HF (HR: 1.99, 95% CI: 1.35 to 2.95), 40% decline in eGFR (HR: 4.81, 95% CI: 3.78 to 6.10) and ESKD (HR: 4.52, 95% CI: 3.00 to 6.82) compared with patients with normoalbuminuria. Increased risk of MACE, HF and 40% decline in eGFR among patients with macroalbuminuria was persistent across subgroups of eGFR 120–30 mL/min/1.73 m².Conclusions In this real-world cohort, uACR was not regularly measured among patients initiating antihypertensive treatment. Nonetheless, the 2-year risks of cardiorenal events were considerably higher among patients with albuminuria compared with patients without.